Signal transducer and activator of transcription 3 is a proviral host factor for hepatitis C virus. Issue 5 (1st October 2013) - McCartney, Erin M.; Helbig, Karla J.; Narayana, Sumudu K.; Eyre, Nicholas S.; Aloia, Amanda L.; Beard, Michael R.
Abstract : Host factors play an important role in all facets of the hepatitis C virus (HCV) life cycle and one such host factor is signal transducer and activator of transcription 3 (STAT3). The HCV core protein has been shown to directly interact with and activate STAT3, while oxidative stress generated during HCV replication in a replicon‐based model also induced STAT3 activation. However, despite these findings the precise role of STAT3 in the HCV life cycle remains unknown. We have established that STAT3 is actively phosphorylated in the presence of replicating HCV. Furthermore, expression of a constitutively active form of STAT3 leads to marked increases in HCV replication, whereas, conversely, chemical inhibition and small interfering RNA (siRNA) knockdown of STAT3 leads to significant decreases in HCV RNA levels. This strongly implicates STAT3 as a proviral host factor. As STAT3 is a transcription factor, up‐regulation of a distinct set of STAT3‐dependent genes may create an environment that is favorable for HCV replication. However, STAT3 has recently been demonstrated to positively regulate microtubule (MT) dynamics, by way of a direct sequestration of the MT depolymerizing protein Stathmin 1 (STMN1), and we provide evidence that STAT3 may exert its effect on the HCV life cycle by way of positive regulation of MT dynamics. Conclusion : We have demonstrated that STAT3 plays a role in the life cycle of HCV and have clarified the role of STAT3 as a proviral host factor. (HEPATOLOGY 2013;58:1558–1568)